8 The effect of tape on ankle joint landing kinematics in subjects with chronic ankle instability. (12th October 2015) - De Ridder, R; Willems, T; Vanrenterghem, J; Robinson, M; Roosen, P
Abstract : Background: Chronic ankle instability is a frequently reported residual pathology which occurs as a result of an initial ankle sprain. Although tape is a commonly used treatment modality, the precise mechanism of efficacy of tape remains unclear. Objective: To evaluate the effect of taping on ankle joint landing kinematics during a jump landing protocol in subjects with chronic ankle instability. Design: Repeated measures. Setting: Laboratory setting. Participants: Twenty-eight participants with chronic ankle instability (10 men and 18 women, age = 22.3 ± 3.0 years, height = 1.73 ± 0.10 m, body mass = 71.0 ± 10.6 kg, FADI = 88.2 ± 7.2%, FADI-S = 69.0 ± 9.6%) participated in this study. Participants were characterised by an initial ankle sprain prohibiting sports participation for at least 3 weeks, episodes of "giving way", repetitive ankle sprains, feelings of instability and weakness around the ankle joint. Interventions: The taping procedure consisted of a double figure-of-8 and a medial heel lock. Main outcome measurements: Unilateral ankle joint 3D kinematics were registered with an eight-camera optoelectronic setup during a forward and side jump with and without tape. After each task, difficulty level and subjective instability at the ankle was documented using a visual analogue scale. Statistical parametric mapping was used to assess the intervention effect of tape on mean joint angles over the entire impact phase from 200 ms prior to 200 ms post landing (normalised to 100% with touch down at 50%). Results: For both the forward and side jump, a less plantar flexed position (respectively from 25%–55%, and 45%–53%), a more everted position (respectively from 30%–45%, and 30%–55%) and a less abducted position (respectively from 0%–15%, and 5%–22%) were found for the taped condition (p < 0.05). The subjective instability level significantly decreased (p < 0.05) when taped, whereas perceived difficulty level was not influenced. Conclusions: The taping protocol significantly altered ankle joint kinematics and improved the subjective stability level in subjects with chronic ankle instability.